Knowledge and Perception of Cardiovascular Risk Factors among Patients with Type II Diabetes Mellitus, 2017 - Titilope Oluwatobiloba Ajepe; Ashiyat Kehinde Akodu; Oluwasegun Adeyemi Ajenipa (Iranian Journal of Health, Safety and Environment, 2022)
Individuals with diabetes are more likely to develop cardiovascular disease (CVD) compared to those without diabetes and when they do, it tends to be more extensive. This study investigated the knowledge and perception of cardiovascular disease risk factors in patients with type II diabetes mellitus (DM). This cross-sectional survey involved 125 patients with type II diabetic Mellitus aged 34-85 years. The heart disease fact questionnaire (HDFQ) and the Perception of Risk of Heart Disease Scale (PRHDS) were used for data collection. Data were analyzed using SPSS version 22.0. The mean score of the knowledge and perception of cardiovascular risk factors among the participants was 11.68±6.71 and 57.47±8.37 respectively. There was a significant difference in the knowledge (p=0.011) and perception (p=0.009) of risk factors of cardiovascular disease between male and female participants. This study shows a fair knowledge and perception of cardiovascular risk factors among patients with type II DM and there was a distinction in the perception and knowledge of cardiovascular risk factors between male and female participants.